2022
DOI: 10.3389/fphar.2022.780991
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Ceftazidime-Avibactam Concentrations in Carbapenem-Resistant K. pneumoniae-Infected Patients With Different Kidney Statuses

Abstract: Aims: Carbapenem-resistant K. pneumoniae (CRKP) is the most common carbapenem-resistant Enterobacteriaceae with high mortality. Ceftazidime-avibactam (CAZ-AVI) has exhibited excellent in vitro activity in vivo against CRKP. However, the efficacy of CAZ-AVI in KPC-producing CRKP-infected patients with different kidney statuses varies, such as renal insufficiency, normal renal function, and augmented renal clearance (ARC). We explored the use of therapeutic drug monitoring (TDM) to evaluate the concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This phenomenon was also observed in a therapeutic drug monitoring (TDM) of CAZ-AVI concentration in CRKP-infected patients with different kidney statuses. In this study, two patients with ARC showed lower ceftazidime and avibactam serum concentrations, even though receiving 2.5 g q6 h CAZ-AVI ( Teng et al, 2022 ). These results implied that increased dosing or dose optimization using prolonged duration may be needed in ARC patients to maintain therapeutic exposure.…”
Section: Pharmacokinetic/pharmacodynamic Targets and Dosage Adjustmen...mentioning
confidence: 65%
“…This phenomenon was also observed in a therapeutic drug monitoring (TDM) of CAZ-AVI concentration in CRKP-infected patients with different kidney statuses. In this study, two patients with ARC showed lower ceftazidime and avibactam serum concentrations, even though receiving 2.5 g q6 h CAZ-AVI ( Teng et al, 2022 ). These results implied that increased dosing or dose optimization using prolonged duration may be needed in ARC patients to maintain therapeutic exposure.…”
Section: Pharmacokinetic/pharmacodynamic Targets and Dosage Adjustmen...mentioning
confidence: 65%
“… 10 However, it was confirmed that the higher the CLCr was, the lower the Css of CAZ‐AVI. In this study, CLCr >130 mL/min was used as the definition of ARC, 27 but patients with a relatively high CLCr in practice, such as 100–129 mL/min, still need to be aware of the possibility of an insufficient dosage of CAZ‐AVI. It also should be noted that the CLCr of the patient with joint PK/PD attainment before medication was 130.63 mL/min, but it dropped rapidly to 65 mL/min on the second day, resulting in a higher Css of CAZ and AVI than that of the other three patients with ARC, suggesting that the CLCr of critically ill patients may vary greatly in clinical conditions and that dynamic monitoring of CLCr and Css of CAZ‐AVI is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…10 However, it was confirmed that the higher the CLCr was, the lower the Css of CAZ-AVI. In this study, CLCr >130 mL/ min was used as the definition of ARC, 27 but patients with a rela-…”
Section: Pathogenmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) of CZA-AVI in four carbapenem-resistant K.pneumoniae -infected patients with different kidney statuses indicated that in one patient with CrCl of 194.98 ml/min/1.73m2 treated with CZA-AVI dose of 2.5 g q6h, sputum and urine cultures turned negative after 3 days. Administration of CZA-AVI (2.5 g q8h on the first day) in another subject with higher CrCl of 295.49 ml/min/1.73m2 did not improve infection, leading to the conclusion that ARC patients need higher daily doses of CAZ-AVI( Teng et al, 2022 ), suggesting that enhanced the dosing internal might be a strategy to attain the PTA Since ceftazidime and avibactam is mainly excreted through the kidney, further research is warranted to establish the impact of ARC on the clinical efficacy of CZA-AVI.…”
Section: Antibacterial Therapy In Arc Patientsmentioning
confidence: 97%